2008
DOI: 10.1007/s00415-008-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for cognitive impairment one year after surgery for aneurysmal subarachnoid hemorrhage

Abstract: The severity of cognitive impairment one year post SAH is predicted by the volume of blood in the subarachnoid space as measured by the Fisher score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 44 publications
4
56
1
2
Order By: Relevance
“…No specific physiopathological mechanism to explain the cognitive dysfunction has been identified, but severity of initial presentation and volume of subarachnoid blood have often been correlated with cognitive outcomes. 7,10,26 The influence of other factors such as hydrocephalus, aneurysm location, treatment method, vasospasm, and ischemic complications on neurocognitive sequelae are less clear. 10,12,16,28 These pathological processes are acute or subacute issues and would not be expected to lead to permanent deficits in the absence of ischemic damage to the neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…No specific physiopathological mechanism to explain the cognitive dysfunction has been identified, but severity of initial presentation and volume of subarachnoid blood have often been correlated with cognitive outcomes. 7,10,26 The influence of other factors such as hydrocephalus, aneurysm location, treatment method, vasospasm, and ischemic complications on neurocognitive sequelae are less clear. 10,12,16,28 These pathological processes are acute or subacute issues and would not be expected to lead to permanent deficits in the absence of ischemic damage to the neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the prevalence of executive dysfunction in aSAH survivors is very wide with estimates ranging from 3% to 76%. 10,[12][13][14][15][16][17][18][19]37 Interestingly, self-reported deficits in executive function do not appear to correlate with results from objective cognitive tests; Ravnik and colleagues 38 found that patients with aSAH reported attentional deficits most frequently, yet patients performed better on tests of attention than on tests of other cognitive domains. Discordance between self-reported cognitive deficits and results from objective cognitive tests has also been reported in other domains, like memory.…”
Section: Executive Functionmentioning
confidence: 99%
“…Findings from most other studies, however, suggest no relationship between ruptured aneurysm location and the profile of cognitive impairment. 13,20,22,32,41,42 Interestingly, Manning and colleagues 43 found that patients with aSAH who had ruptured anterior communicating artery aneurysms (proximal to the frontal lobes) performed significantly better than patients with nonanterior aneurysms on the Tower of London task, 44 a test of executive function. The relationship between aneurysm location and the profile of cognitive impairment thus remains unclear.…”
Section: Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors claim that there is no correlation between these two aspects (8,15,16), whereas others state the opposite (17) .…”
Section: Introductionmentioning
confidence: 99%